Tofta i Tjeldsund: Övervakning av grävning på boplassområde ifrån medeltid - Cerbing, Mikael (Tromura, 2026)
In late autumn 2025, the Arctic University Museum of Norway carried out archaeological monitoring in Tjeldsund municipality in connection with the expansion of a ditch that passed through a previously known farm mound. The farm mound “Tofta” is the first registered farm mound in Northern Norway, and it was investigated and supposedly levelled in 1874–1875.The monitoring revealed part of a possible intact cultural layer in the most northwestern part of the ditch. A thinner layer of disturbed farm mound mass could be detected in several places in the ditch, and some examples of finds and two charcoal samples from the possibly intact layer were collected. Otherwise, it seems that at least this part of the farm mound was levelled in the way described in texts from the 19th century.
Keywords: archaeology; monitoring; farm mound; cultural layers; medieval period; northern norway